A dimensão subjetiva da atividade de mediação de conflitos nas escolas: um estudo das significações constituídos por professoras mediadoras - Mennocchi, Lauren Mariana (2019)
The School Protection System (SPS) of the State Department of Education of São Paulo (SDE SP) for conflict prevention and the fight against violence in the school environment has established, since 2010, the role of the school and community mediator teacher (SCMT), with a double objective: (a) to accompany the students in the coexistence with other members of the various school segments; (b) to develop a pedagogical project that amplifies factors of protection and diminishes possible factors of vulnerability and conflicts inherent to this coexistence. In view of the recent proposal, its uncertainties and its many challenges, the present research will seek to identify the senses and meanings of the activity of conflict mediation among SCMTs and will seek to deepen the understanding of what is meant by "school conflicts", from the theoretical-methodological framework of historical and dialectical materialism. The information for the investigation of the "nuclei of signification" was produced in individual and collective interviews with PMECs and SPE leaders of the Teaching Board of São José dos Campos, Vale do Paraíba Paulista. In order to contribute to the development of new empirical information production strategies, the collective interviews of this research were conducted through the use of artistic mediations and the socialdrama technique, since art can be used as a mediating psychological instrument that enables the subject to the development of two higher psychological functions, of which consciousness stands out. Even without the intention of constituting an intervention, the stage of production of information constitutes a moment of reflection, a unification between doing, feeling and thinking for the participants and a potential instrument of access to the affects of mediators, a fundamental dimension when one intends to study the meanings and motives of human activity. Based on the assumptions of Socio-Historical Psychology, this research will analyse the senses and meanings of conflicts, students and their relatives, and ways of performing mediation in school, in order to grasp the subjective dimension of educational reality and, therefore, the senses and meanings constituted by teachers about their activity and its political and pedagogical function in the context of the current policies of school protection and fight against violence. It is expected that the results achieved will contribute to the understanding of school conflicts, as well as to the effective practice of teacher mediation and the strengthening of school institutions as spaces for dialogue and social transformation